Scale-dependent fracture networks. (December 2022) - Forstner, Stephanie R.; Laubach, Stephen E.
Abstract: Using examples of regional opening-mode fractures in sandstones from the Cambrian Flathead Formation, Wyoming, we show that quartz deposits preferentially fill fractures up to ca. 0.05 mm wide and fractures transition from being mostly sealed to mostly open over a narrow size range of opening displacements from 0.05 to 0.1 mm. In our example, although isolated (I-node) dominated networks have some trace connectivity, the effective connectivity for fluid flow is likely greatly reduced by quartz cementation. Trace connectivity at microscopic and outcrop scale is similar, but most porosity is found in outcrop-scale fractures. Near faults, trace connectivity increases as initially wide porous fractures preferentially shear and wing cracks form, increasing fracture intersections (Y-nodes). However, pore space is lost due to the development of microbreccia. Macro-scale trace connectivity increases, but porous connectivity diminishes and thus potential for fluid flow is markedly lower. Connectivity descriptions should include accurate measures of widths and lengths and use nodes that reflect scale and diagenesis. We propose new rule-based node descriptions to measure diagenesis sensitive connections within the context of current field practices. Under diagenetic conditions between ca. 50°C–250°C differential infill makes network porosity, and thus permeability and strength, scale dependent. Highlights: Quartz deposits in sandstone fracture networks reduce porosity continuity. Cements control fracture porosity, reactivation potential and network connectivity. Precipitation kinetics makes network strength and permeability scale dependent. Contingent nodes (C-nodes) represent connections susceptible to sealing by quartz. Connectivity analyses should include C-nodes to account for scale and diagenesis.